Data Quality Evaluation of Photovoltaic Power Station based on Entropy Weight Method and Grey Comprehensive Evaluation Method. Issue 1 (1st December 2022) - Xie, Hongbin; Ma, Xiaoguang; Zhao, Junyong; Han, Bitong; Shan, Yu
Abstract: The increasing necessity of renewable energy utilization has fueled the successful development of photovoltaic power generation technology. Distributed photovoltaic power stations have been rapidly promoted because of their small installed capacity and low initial investment costs. Scientific and comprehensive data evaluation of distributed PV is conducive to improving the operational efficiency of the power station. An index evaluation system is constructed for distributed power station data in each province. The entropy weighting method is used to determine the weights of different dimensions. Then, the data quality evaluation level is contrasted with the help of the gray evaluation method. Simulations of the proposed method were conducted. Finally, the results showed that the data of the tested distributed PV were at an excellent level, which verified the applicability of the method. In addition, the causes of data quality deficiencies are preliminarily explored.